Development of multiplex cross displacement amplification combined with lateral flow biosensor assay for detection of virulent shigella sonnei - Wang, Yonglu; He, Ziqiang; Ablimit, Patigul; Ji, Shunshi; Jin, Dong (Frontiers in Cellular and Infection Microbiology, 2022)
Shigella sonnei is the leading species of Shigella spp. in developed areas and the second most common species in economically poor countries. In this study, multiple cross displacement amplification (MCDA), combined with the lateral flow biosensor (LFB) is utilized to detect virulent S. sonnei strains with ipaH and wbgX genes. This multiplex MCDA-LFB assay could detect as low as 1 pg/μL with wbgX and 10 fg/μL with ipaH genes in pure cultures at 63 °C within 25 min. The sensitivity of this assay in the simulated fecal samples was ~37 CFU of virulent S. sonnei and ~3.7 CFU of Shigella spp. and enteroinvasive E. coli, which also indicated the application of this assay in clinical fecal samples. The specificity of this multiplex MCDA-LFB assay demonstrated with 59 reference strains was 100%. This multiplex MCDA-LBF assay could differentiate virulent S. sonnei from other Shigella spp. and enteroinvasive E. coli with the application of 99 clinical isolates. In sum, we developed a multiplex MCDA-LFB assay for rapid, convenient, point-of-care, and accurate identification of virulent S. sonnei at a constant temperature within 25 min without the use of expensive equipment.